Biochemical Constituent of Ginkgo biloba (Seed) 80% Methanol Extract Inhibits Cholinesterase Enzymes in Javanese Medaka (Oryzias javanicus) Model - Ibrahim Hassan; Wan Norhamidah Wan Ibrahim; Ferdaus Mohamat Yusuf; Siti Aqlima Ahmad; Syahida Ahmad (Journal of Toxicology)
Background. Pathophysiological changes leading to the death of nerve cells present in the brain and spinal cord are referred to as neurodegenerative diseases. Presently, treatment of these diseases is not effective and encounters many challenges due to the cost of drug and side effects. Thus, the search for the alternative agents to replace synthetic drugs is in high demand. Therefore, the aim of this study is to evaluate the anticholinesterase properties of Ginkgo biloba seed. Methods. The seed was extracted with 80% methanol. Toxicity studies and evaluation of anticholinesterase activities were carried out in adult Javanese medaka (Oryzias javanicus). Phytochemical study to identify the bioactive lead constituents of the crude extract was also carried out using high performance liquid chromatography (HPLC). Results. The result shows activities with high significant differences at P<0.001 between the treated and nontreated groups. A bioactive compound (vitaxin) was identified with the aid of HPLC method. Conclusion. The presence of bioactive compound vitaxin is among the major secondary metabolites that contribute to increasing activities of this plant extract. High anticholinesterase activities and low toxicity effect of this plant show its benefit to be used as natural medicine or supplements.